Terrapsychological inquiry: restorying our relationship with nature, place, and planet - Chalquist, Craig, 1963- (Abingdon, Oxon; New York, USA: Routledge, Taylor & Francis Group, 2024)
"Terrapsychological Inquiry is a path of storied, imaginative research that takes seriously our intense inner responses to the state of the natural world. This place-rooted approach studies, from the standpoint of lived experience, how the world gets into the heart. Oceans and skies, trees and hills, rivers and soils, and even built things like houses, cities, ports, and planes: How do they show up for us inwardly? How do our moods, feelings, and dreams reflect what happens in the world? Terrapsychological Inquiry evolved over a decade of exploration by graduate students, instructors, ceremonialists, workshop leaders and presenters, and other practitioners of embodied creativity to offer an Earth-honoring mode of storied qualitative inquiry, one that transforms all involved from passive spectators of the doings of the world into active, sensitive participants. Learn how to use this methodology of earthly reenchantment in a variety of settings inside and outside academia and by doing so reenter an animate world. This new edition has been revised throughout and offers fresh insights into how Terrapsychological Inquiry, a field with roots in depth psychology, ecopsychology, and Hermetic philosophy, can also be used as an ecospiritual path. Thoroughly updated with a new chapter and added discussion questions and exercises at the end of each chapter, this introduction to an evolving research methodology will be of great interest to students and scholars of environmental psychology, ecotherapy, and environment and sustainability studies more generally"--
"First edition published by Routledge 2020"--Title page verso.
Includes bibliographical references and index.
Keywords: Environmental psychology